If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -6 = 3r + -8 Reorder the terms: -6 + r = 3r + -8 Reorder the terms: -6 + r = -8 + 3r Solving -6 + r = -8 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. -6 + r + -3r = -8 + 3r + -3r Combine like terms: r + -3r = -2r -6 + -2r = -8 + 3r + -3r Combine like terms: 3r + -3r = 0 -6 + -2r = -8 + 0 -6 + -2r = -8 Add '6' to each side of the equation. -6 + 6 + -2r = -8 + 6 Combine like terms: -6 + 6 = 0 0 + -2r = -8 + 6 -2r = -8 + 6 Combine like terms: -8 + 6 = -2 -2r = -2 Divide each side by '-2'. r = 1 Simplifying r = 1
| g(3)=2/3x-1 | | (7x-8)7=(6x-4)6 | | 4x-10=69 | | 25/10000 | | 202/2= | | 202/2 | | b^2+3b-972=0 | | 164+38= | | -9(y+9)=-10y | | 23+38= | | W^2+7w=44 | | 3x+8+6x=32 | | (4a+5)(7a+2)=0 | | -1=4/6(4)+b | | 164-38= | | 55+1+54x+70=180 | | 16t^2-48t+h=0 | | 3x+21=5x+10 | | 6y-y^2=4 | | (5x-8)5=(14x-1)5 | | 0=-3/4(-3)+b | | z=ax+by+a | | -67+2.5x=15 | | 3x+-1= | | 4x+32=2x+30 | | 10x+10=10x+20 | | 134+67= | | 8u=-10b+80 | | 67*2= | | -67+2.5x=5 | | 2x^2-16xy-9x+72y= | | x+x*2=201 |